(3QSGdI aj GdaUOs - (3CMeO Hf eMeO CHh GdMSf GdWHQj, fMh (B360 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hdi GdMeO Efj QCjJ CWHGA LQLGf haUGOge jCJhf GdTF ef ZjQ JejjR hbO cfJ UfaJ ebGdI HGdQi , GdaUGOjf EfJaYhG HgG , hde jHb efge CMO EdG hGfJSNgG hMaXgG s
(3BNQgG (B:s
(3hjLH Cf jchf GdEfSGf Ydi MPQ ef Gf jbY Ydjg TF bO jfbHV Ch jfaJM KGfjkG, aEf ajg NWQkG YXjekG hGddg jhabfG GdQTGO hGdUhGH aj LejY GdCehQ , hgh MSHfG hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B103 - (3U(B118s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B108 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj edj (B(1538) s
Keywords: (3GdWHs